P70 Management of pleural effusions: Are healthcare professionals adequately trained?. (14th November 2013) - Ross, CL; Dimock, R; Chotai, A; Meeajan, R; Wan, T; Finney, L; Elkin, SL
Abstract : Introduction and Objectives: Management of pleural effusions is evolving with the introduction of a Best Practice Tariff for unilateral effusions and increasing use of thoracic ultrasound. However, transitions have been slow to filter through to clinical practice. This improvement project investigated the current management of pleural effusions within our Trust. Methods: We conducted: 1) An audit of all procedures for pleural effusions between 01.09.12 and 30.11.12; 2) A survey of junior doctors to establish their training provision, current practice and knowledge; and 3) A survey of acute medicine, respiratory, cardiothoracic and oncology nurses who regularly care for patients with effusions. Results: The audit reviewed 52 chest drains and 20 aspirations across 3 sites. Documentation of consent occurred in 39% of cases. Ultrasound was used in 79% of drains, but 26% of cases still used a remote 'X marks the spot' approach. 27% of procedures were done out-of-hours and 34% of patients waited over 12 hours for a chest x-ray following drain insertion. 61 junior doctors responded to the survey: 44% did not use sterile gowns when inserting drains; 11% did not use sterile gloves. No medical doctors had acquired level 1 ultrasound competence. Of the 31 nurses surveyed: 19% did not know the significance of a 'bubbling' drain; 39% did not know what 'swinging' indicated; 48% did not equate closing a 3-way tap with clamping a drain; and 26% were not aware chest drain bottles should be kept below the insertion point. 54% had never received any training regarding chest drain management. 45% of doctors and 58% of nurses were unaware of local guidelines. Conclusions: It is unlikely our findings are grossly different to practice in other inner city Trusts. With high staff turnaround, regular training for those caring for people with pleural effusions is clearly needed. Training should focus on aspects of patient safety such as image-guidance, aseptic technique and drain management. This study has led to the introduction of new local guidelines and pathways, creation of a pleural procedure kit to include aseptic equipment, implementation of an effusion bundle, and training sessions for doctors and nurses.